2001
DOI: 10.1136/jmg.38.12.810
|View full text |Cite
|
Sign up to set email alerts
|

Silver-Russell syndrome: a dissection of the genetic aetiology and candidate chromosomal regions

Abstract: The main features of Silver-Russell syndrome (SRS) are pre-and postnatal growth restriction and a characteristic small, triangular face. SRS is also accompanied by other dysmorphic features including fifth finger clinodactyly and skeletal asymmetry. The disorder is clinically and genetically heterogeneous, and various modes of inheritance and abnormalities involving chromosomes 7, 8, 15, 17, and 18 have been associated with SRS and SRS-like cases. However, only chromosomes 7 and 17 have been consistently impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
84
3
4

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(94 citation statements)
references
References 86 publications
(78 reference statements)
3
84
3
4
Order By: Relevance
“…The prognosis for SRS is favourable, but for a diminished adult size. (20,21) Usually, diagnosis of SRS is established when growth retardation, facial dysmorphism and one or more of the minor features are present. Diagnosis may be subjective, however, and SRS could comprise different disorders with clinically similar phenotypes, or could result from disruption of different components of a single pathway.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognosis for SRS is favourable, but for a diminished adult size. (20,21) Usually, diagnosis of SRS is established when growth retardation, facial dysmorphism and one or more of the minor features are present. Diagnosis may be subjective, however, and SRS could comprise different disorders with clinically similar phenotypes, or could result from disruption of different components of a single pathway.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are families in which genetic transmission of the disease has been observed, and predominant maternal transmission in some of them had suggested that genomic imprinting could be involved. (21) In addition, specific chromosomal abnormalities have been described in some cases, involving different chromosomes. For example, several SRS families were identified with maternal duplications of chromosome 11p15, but without any apparent genetic mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Silver-Russell syndrome (SRS) is a congenital developmental disorder characterized by pre-and postnatal growth failure, body asymmetry, relative macrocephaly, triangular face, and fifth-finger clinodactyly [1]. Precocious puberty is also occasionally observed in this condition.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of unmasking of a recessive allele(s) by isodisomy is unlikely, because both isodisomy and heterodisomy have been found in SRS with no common isodisomic region [2]. Furthermore, molecular studies in several key patients have suggested two separate candidate regions for SRS, 7p11.2-p13 [3] and 7q31-qter [4], and several candidate genes such as GRB10 (growth factor receptor-bound protein 10) on 7p12 and PEG1/MEST (paternally expressed gene 1/mesoderm-specific transcript) on 7q32.2 have been identified [1], although the gene(s) responsible for SRS has not been identified to date. In addition, recent studies have shown hypomethylation of the differentially methylated region (DMR) located upstream of H19 (H19-DMR) in a considerable fraction of SRS patients, providing further support for the relevance of imprinting failure in SRS [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation